Molecular identification of individual and seasonal variation in incidental ingestion of arthropods by free-ranging goats - Berman, Tali Sarah; Inbar, Moshe (Frontiers in Ecology and Evolution, 2023)
The extent of direct interactions between large mammalian herbivores (LMH) and plant-dwelling arthropods (PDA), i.e., the ingestion of PDA by LMH, remains largely unexplored. Grazing LMH may ingest a variety of PDA, yet, it is unknown how different foraging strategies (i.e., browsing, grazing, etc.) influence the ingestion of PDA or whether individual variation within herds affects it. Here we examine how individual variation within a herd of browsing LMH impacts PDA ingestion. This was done using a DNA metabarcoding analysis on feces collected monthly from marked individuals within a herd of free-ranging goats. We found that goats frequently ingest PDA while feeding (all samples contains PDA), including a complex food-chain of herbivores, predators and parasites, which differed over the season and among individual goats. In total, 63 families of insects and 9 families of arachnids from 15 orders were ingested by the goats. Most ingested PDA were herbivores with reduced mobility, such as immature or sessile species. Highly mobile and noxious PDA were rarely detected. We show for the first time that ingestion of PDA by LMH is influenced by seasonal and individual variation within the herd and that it is common among LMH, regardless of feeding strategy or habitat.